Erector Spinae Plane Blocks for the Early Analgesia of Rib Fractures in Trauma (ESPEAR): protocol for a multicentre pilot randomised controlled trial with feasibility and embedded qualitative assessment. Issue 9 (21st September 2022) - Hewson, David W; Nightingale, Jessica; Ogollah, Reuben; Ollivere, Benjamin J; Costa, Matthew L; Craxford, Simon; Bates, Peter; Bedforth, Nigel M
Abstract : Introduction: Patients with rib fractures commonly experience significant acute pain and are at risk of hypoxia, retained secretions, respiratory failure and death. Effective analgesia improves these outcomes. There is widespread variation in analgesic treatments given to patients including oral, intravenous and epidural routes of administration. Erector spinae plane (ESP) blockade, a novel regional analgesic technique, may be effective, but high-quality evidence is lacking. Methods and analysis: To determine if a definitive trial of ESP blockade in rib fractures is possible, we are conducting a multicentre, randomised controlled pilot study with feasibility and qualitative assessment. Fifty adult patients with rib fractures will be randomised in a 1:1 ratio to ESP blockade with multimodal analgesia or placebo ESP blockade with multimodal analgesia. Participants and outcome assessors will be blinded. The primary feasibility outcomes are recruitment rate, retention rate and trial acceptability assessed by interview. Ethics and dissemination: The study was approved by the Oxford B Research Ethics Committee on 22 February 2022 (REC reference: 22/SC/0005). All participants will provide written consent. Trial results will be reported via peer review and to grant funders. Trial registration number: ISRCTN49307616 .